2020
DOI: 10.1101/2020.09.09.20184143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Early Hydroxychloroquine-based Therapy in COVID-19 Patients in Ambulatory Care Settings: A Nationwide Prospective Cohort Study

Abstract: BACKGROUND: Currently, there is no proven effective therapy nor vaccine for the treatment of SARS-CoV-2. Evidence regarding the potential benefit of early administration of hydroxychloroquine (HCQ) therapy in symptomatic patients with Coronavirus Disease (COVID-19) is not clear. METHODS: This observational prospective cohort study took place in 238 ambulatory fever clinics in Saudi Arabia, which followed the Ministry of Health (MOH) COVID-19 treatment guideline. This guideline included multiple treatment optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…Specifically, we tested and observed both additive and interactive associations of HCQ and Covid-19 subtypes. Indeed, the high risk cluster was consistently associated with increased mortality across all models, while treatment with HCQ was generally associated with a halving of death risk, in line with previous evidence from both observational [6][7][8][9][10][11][12][13] and intervention studies [19]. While we already reported evidence suggesting a protective influence of HCQ against mortality in a largely overlapping sample [13], here we have further deepened this relationship by testing and reporting a significant association between cluster-by-HCQ interaction and mortality, which was driven by a differential association within the two clusters.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Specifically, we tested and observed both additive and interactive associations of HCQ and Covid-19 subtypes. Indeed, the high risk cluster was consistently associated with increased mortality across all models, while treatment with HCQ was generally associated with a halving of death risk, in line with previous evidence from both observational [6][7][8][9][10][11][12][13] and intervention studies [19]. While we already reported evidence suggesting a protective influence of HCQ against mortality in a largely overlapping sample [13], here we have further deepened this relationship by testing and reporting a significant association between cluster-by-HCQ interaction and mortality, which was driven by a differential association within the two clusters.…”
Section: Discussionsupporting
confidence: 85%
“…Despite these elements and initial suggestive evidence of efficacy based on daily clinical practice, in the last months the potential benefit of HCQ for Covid-19 patients has been harshly debated [3,5]. In particular, evidence supporting protective effects from observational studies [6][7][8][9][10][11][12][13] was in contrast with that suggesting no effect at all by recent randomized clinical trials (RCTs) [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Data from 3 independent cohorts were extracted from the study of Kim et al [ 46 ]; 7 articles were not published in peer reviewed journals; 4 observational studies reported unadjusted relative risks for the association between HCQ and mortality; 13 studies have been conducted in Europe, 17 in North America (Canada, USA or Mexico), 3 in Asia (China, Saudi Arabia) and three in other countries. The outcome considered was total mortality, with the exception of Geleris et al [ 18 ] in which the authors used a combined endpoint formed by intubation or death; the mortality was intra-hospital, with the exception of the studies [ 28 , 33 , 35 , 36 ], in which death was all-cause, all-location. All studies included hospitalized patients, with the exclusion of three ones which included ambulatory [ 28 , 36 ] or non-hospitalized individuals [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with the results of several non-randomized controlled evaluations of HCQ outpatient therapy for COVID-19, which have reported substantial effectiveness. 4 5 6 7 8 9 In addition, a number of studies examining HCQ use in the hospitalized setting—particularly use starting within 24-48 hours of admission—have also shown benefit. 19 20 21 22 23 24 That modern, well-conducted non-randomized trials and observational studies would yield results similar to those of RCTs is not surprising as it is the common finding across numerous medical disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of non-randomized but controlled trials have now shown benefit of HCQ when used early for treatment of high-risk outpatients. 4 5 6 7 8 9 Various randomized trials of HCQ for pre-exposure prophylaxis, post-exposure prophylaxis, and outpatient treatment have been performed. Individually, these clinical trials have yielded estimates of effectiveness that have not reached statistical significance.…”
Section: Introductionmentioning
confidence: 99%